Fabrication, microstructures and properties of 50 vol.-% SiCp/6061Al composites via a pressureless sintering technique. (1st January 2018) - Mao, Xuezhi; Hong, Yu; Wang, Binhao; Liu, Junwu; Zhang, Yujun; Feng, Dong; Yang, Lei; Shi, Changdong; Wu, Yucheng; Tang, Wenming
ABSTRACT: Commercial F500 SiC powder and 6061 Al powder were chosen to fabricate the 50 vol.-% SiCp/6061Al composites via pressureless sintering. Effects of pre-treatment of the SiC powder and sintering temperature on the microstructures and properties of the composites were studied. Densification mechanism and interfacial reaction of the composites were also investigated. The results show that the composites have a high sintering ability and a low interfacial reaction activity. The density, bending strength and thermal conductivity of the composites are all sensitive to the sintering temperature. The composites sintered at 680°C are nearly fully dense and have the following optimal properties: the relative density of 98.5%, the bending strength of 495 MPa, the TC of 153 W/(m K) and the coefficient of thermal expansion of 8.1 × 10 −6 /°C (50–100°C), which are superior to most of the SiCp/Al composites of the similar composition reported previously.